The role of home-based records in the establishment of a continuum of care for mothers, newborns, and children in Indonesia - Keiko Osaki; Tomoko Hattori; Soewarta Kosen (Taylor & Francis Group, 2013)
Background: The provision of appropriate care along the continuum of maternal, newborn, and child health (MNCH) service delivery is a challenge in developing countries. To improve this, in the 1990s, Indonesia introduced the maternal and child health (MCH) handbook, as an integrated form of parallel home-based records. Objective: This study aimed to identify the roles of home-based records both before and after childbirth, especially in provinces where the MCH handbook (MCHHB) was extensively promoted, by examining their association with MNCH service uptake. Design: This was a cross-sectional study using nationally representative data sets, the Indonesia Demographic and Health Surveys (IDHSs) from 1997, 2002–2003, and 2007. The IDHS identifies respondents’ ownership of home-based records before and after childbirth. Multivariate logistic regression was used to examine associations between record ownership and service utilisation in national data and data from two provinces, West Sumatra and North Sulawesi, where ownership of pre- and post-natal records served as a proxy for MCHHB ownership. Results: Pre- and post-natal record ownership increased from 1997 to 2007. Provincial data from 2007 showed that handbook ownership was associated with having delivery assisted by trained personnel [adjusted odds ratio (aOR): 2.12, 95% confidence interval (CI): 1.05–4.25], receiving maternal care (aOR: 3.92, 95% CI: 2.35–6.52), completing 12 doses of child immunisation for seven diseases (aOR: 4.86, 95% CI: 2.37–9.95), and having immunisation before and after childbirth (aOR: 5.40, 95% CI: 2.28–12.76), whereas national data showed that service utilisation was associated with ownership of both records compared with owning a single record or none. Conclusion: Our results suggest that pre- and post-natal home-based record use may be effective for ensuring service utilisation. In addition, since the handbook is an efficient home-based record for use throughout children's life courses, it could be an effective tool for promoting the continuum of MNCH care in Indonesia.